Superfood and Functional Food - An Overview of Their Processing and Utilization 2017
DOI: 10.5772/66123
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Biofortification and the Problem of its Safety

Abstract: Selenium is an essential mineral element to humans and animals because it is an important component of selenoproteins that are important for functioning of the metabolism. Because of poor soil conditions in various regions of the world, the enrichment of edible plants with selenium via the biofortification strategy has been implemented. However, selenium in the context of plant mineral nutrition appears twofold due to its biofortifying character at low concentrations and toxicity at high concentrations. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…brassica species: pak choi and cabbage) normally accumulate more Se than legumes (beans), followed by cereals (wheat and rice). The Se concentration accumulated in fruits is generally low, whereas high concentrations (ranging from 0.03-512 mg/kg) have been reported in Brazil nuts as a result of natural biofortification (Prado et al, 2017). showed that the efficiency of Se foliar applications is on average 8 times more efficient than soil applied fertilizers (Ros et al, 2016).…”
Section: Approaches For Addressing Se Deficiency -Biofortificationmentioning
confidence: 99%
See 1 more Smart Citation
“…brassica species: pak choi and cabbage) normally accumulate more Se than legumes (beans), followed by cereals (wheat and rice). The Se concentration accumulated in fruits is generally low, whereas high concentrations (ranging from 0.03-512 mg/kg) have been reported in Brazil nuts as a result of natural biofortification (Prado et al, 2017). showed that the efficiency of Se foliar applications is on average 8 times more efficient than soil applied fertilizers (Ros et al, 2016).…”
Section: Approaches For Addressing Se Deficiency -Biofortificationmentioning
confidence: 99%
“…Se). Although Se is not an essential trace element for plants, it presents chemical similarity to S, and both elements have the same carrier membranes and biochemical pathways of assimilation in plant uptake (Prado et al, 2017).…”
Section: Approaches For Addressing Se Deficiency -Biofortificationmentioning
confidence: 99%